Analysis of the Effect of Leadership Style, Financial Rewards and Work Environment on Turnover Intention Mediated by Job Satisfaction (Empirical Study: Private Bank Jakarta Employees) - Suwandy Thu; Chandra Wibowo Widhianto (Pelopor Publikasi Akademika, 2023)
This study aimed to investigate the impact of leadership style, financial rewards, and work environment on turnover intention, with job satisfaction as a mediating factor among employees of private Bank/Bank BDI Jakarta. The research adopted a quantitative approach with hypothesis testing, collecting primary data through valid questionnaires filled out by 330 respondents, specifically employees of Bank BDI, using Stratified Sampling. Data analysis was conducted using Structural Equation Model (SEM) with Smart PLS software version 3.0. The findings indicate a positive and significant influence of leadership style, financial rewards, and work environment on turnover intention, mediated by job satisfaction among Bank BDI Jakarta employees. However, the direct testing of leadership style, financial rewards, and work environment did not demonstrate a significant impact on turnover intention, suggesting the presence of other significant factors influencing turnover intention beyond the three independent variables examined. In conclusion, job satisfaction plays a pivotal role in determining turnover intention, and enhancing job satisfaction can effectively reduce turnover rates among Bank BDI Jakarta employees. However, it's worth noting that this study's limitation lies in its sample being limited to Jakarta, making it difficult to generalize the findings to all branch offices due to potential variations in characteristics and cultures across different regions.